PENGARUH EARNING POWER DAN LEVERAGE TERHADAP MANAJEMEN LABA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2019 - Dini Mariani; Catur Martian Fajar (Jurnal Financia : Akuntansi dan Keuangan, 2021)
Earning Power and Leverage is one of the factors that can cause earnings management and can reduce the credibility of financial statements in decision making because earnings management is a form of manipulation that occurs in the company by managers. The purpose of this study was to determine the effect of earnings power and leverage on earnings management of the food and beverage sub sector listed on the Indonesia Stock Exchange. Based on the variables studied, this type of research is a quantitative research with descriptive verification research type. The results showed that earning power had a partially insignificant effect while leverage significantly affected earnings management. The results of simultaneous testing of the two independent variables significantly influence earnings management. Keywords: Earning Power, Leverage and Profit Management.